2014
DOI: 10.1093/neuonc/not307
|View full text |Cite
|
Sign up to set email alerts
|

MiR-196a exerts its oncogenic effect in glioblastoma multiforme by inhibition of IκBα both in vitro and in vivo

Abstract: MiR-196a exerts its oncogenic effect in GBM by inhibiting IκBα both in vitro and in vivo. Our findings provide new insights into the pathogenesis of GBM and indicate that miR-196a may predict clinical outcome of GBM patients and serve as a new therapeutic target for GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…These findings are mostly, but not always consistent with previous studies showing increased expression of miR-196a2 in several solid tumors [7], including esophageal adenocarcinoma [46], gastric cancer [9,[47][48][49], colorectal cancer [50][51][52], pancreatic cancer [53][54][55], hepatocellular carcinoma [56], breast cancer [57][58][59], cervical cancer [8,60], ovarian cancer [61], lung cancer [57,62,63], bone cancer [12,64], and malignant glioblastoma [22,65]. In contrast, miR-196a2 expression was reported to be down-regulated in prostate cancer cell lines [57] and melanoma cell lines [66] or tissues [67].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are mostly, but not always consistent with previous studies showing increased expression of miR-196a2 in several solid tumors [7], including esophageal adenocarcinoma [46], gastric cancer [9,[47][48][49], colorectal cancer [50][51][52], pancreatic cancer [53][54][55], hepatocellular carcinoma [56], breast cancer [57][58][59], cervical cancer [8,60], ovarian cancer [61], lung cancer [57,62,63], bone cancer [12,64], and malignant glioblastoma [22,65]. In contrast, miR-196a2 expression was reported to be down-regulated in prostate cancer cell lines [57] and melanoma cell lines [66] or tissues [67].…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with previous studies reporting that upregulation of miR-196a was found to be correlated with advanced tumor stage and poor overall and recurrence-free survival in many cancer patients [8,52]. This upregulation could suppress annexin A1; an inhibitor of cell proliferation, and mediator of apoptosis and anchorage-independent growth [68], enhance G1/S-phase transition and the proliferative ability of cancer cells through targeting FOXO1 and p27Kip1; two key effectors of the PI3K/Akt signaling pathway that regulates cell proliferation and has been addressed as a therapeutic target [8,9], up-regulate the ubiquitin-conjugating enzyme E2C (UBE2C) proto-oncogene [83], inhibit Bach1 (a basic leucine zipper mammalian transcriptional repressor) and upregulate hemeoxygenase 1 in HCV-related HCC [84], inhibit IjBa, which binds and tethers NF-jB in the cytoplasm; leading to translocation of the later into the nucleus where it activates a variety of target genes such as apoptosis-related genes Bax and Bcl-2 that regulate activation of caspase-3 [65], and regulates the Wnt-Fgf-Notch signaling pathways [85] that are commonly associated with tissue invasion and metastasis [86]. Together, these findings suggest that miR-196a2 could be a favorable prognostic biomarker in a cancer-specific pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as elevated levels of TRADD and loss of miR-31 are both observed in Mesenchymal GBM, our data may provide an explanation for this observed co-occurrence. The above miRs provide an interesting sampling of the miRs identified as regulating NF-κB, but the list of such miRs is long and growing [6163]. …”
Section: Nf-κb In Gbmmentioning
confidence: 99%
“…Currently three miR-196 members (miR-196a-1, miR-196a-2 and miR-196b) have been identified, and miR-196a genes are located within the HOX gene clusters (Chen et al, 2011). miR-196a has been reported to promote tumorigenesis in multiple types of cancers such as pancreatic cancer, glioma, lung cancer, and ovarian cancer (Kong et al, 2011;Liu et al, 2012;Yang et al, 2014;Fan et al, 2015). Furthermore, serum levels of miR-196a were significantly increased in patients with pancreatic cancer, and higher serum levels were associated with advanced clinical stage and shorter survival time (Kong et al, 2011).…”
Section: Introducationmentioning
confidence: 99%